Starch supplementation modulates amylase enzymatic properties and amylase B mRNA level in the digestive gland of the Pacific oyster Crassostrea gigas. - Huvet, Arnaud; Jeffroy, F.; Daniel, J. Y.; Quéré, C.; Le Souchu, P.; van Wormhoudt, A.; Boudry, Pierre; Moal, J.; Samain, J. F. (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2012)
International audience In the oyster Crassostrea gigas consumption-related traits, amylase properties and growth were found to be linked through genotypes that differed for polymorphism in the two amylase genes AMYA and AMYB. Modulation of AMYA mRNA level had already been observed in response to food availability, whereas the functional role of AMYB was still unknown. To improve knowledge about the regulation of amylase expression in C. gigas and the respective roles of the two genes, we made an assay of amylase expression at mRNA and enzymatic levels in the digestive gland of oysters that had received dietary supplements of starch. After 18 days, a significant increase of translatable mRNA for AMYB was observed, with a correlated increase in Michaelis-Menten constant Km values and a decrease in total amylase activity. This modulation is the first evidence of observable functioning of AMYB in digestive processes. Amylase B is suggested to display a higher Km than amylase A, offering a means of adapting to high substrate concentrations. The highest starch supplement level (10 mgL(-1)) induced alteration in oyster physiology. The 1 mgL(-1) treatment should be tested as a practical food supplement that could lead to growth benefits for oysters.